Rapid and Reversible Recruitment of Early Visual Cortex for Touch - Merabet, Lotfi B.; Hamilton, Roy; Schlaug, Gottfried; Swisher, Jascha D.; Kiriakopoulos, Elaine T.; Pitskel, Naomi B.; Kauffman, Thomas; Pascual-Leone, Alvaro (PloS one, 2008)
The loss of vision has been associated with enhanced performance in non-visual tasks such as tactile discrimination and sound localization. Current evidence suggests that these functional gains are linked to the recruitment of the occipital visual cortex for non-visual processing, but the neurophysiological mechanisms underlying these crossmodal changes remain uncertain. One possible explanation is that visual deprivation is associated with an unmasking of non-visual input into visual cortex. We investigated the effect of sudden, complete and prolonged visual deprivation (five days) in normally sighted adult individuals while they were immersed in an intensive tactile training program. Following the five-day period, blindfolded subjects performed better on a Braille character discrimination task. In the blindfold group, serial fMRI scans revealed an increase in BOLD signal within the occipital cortex in response to tactile stimulation after five days of complete visual deprivation. This increase in signal was no longer present 24 hours after blindfold removal. Finally, reversible disruption of occipital cortex function on the fifth day (by repetitive transcranial magnetic stimulation; rTMS) impaired Braille character recognition ability in the blindfold group but not in non-blindfolded controls. This disruptive effect was no longer evident once the blindfold had been removed for 24 hours. Overall, our findings suggest that sudden and complete visual deprivation in normally sighted individuals can lead to profound, but rapidly reversible, neuroplastic changes by which the occipital cortex becomes engaged in processing of non-visual information. The speed and dynamic nature of the observed changes suggests that normally inhibited or masked functions in the sighted are revealed by visual loss. The unmasking of pre-existing connections and shifts in connectivity represent rapid, early plastic changes, which presumably can lead, if sustained and reinforced, to slower developing, but more permanent structural changes, such as the establishment of new neural connections in the blind.